2003
DOI: 10.1007/s00134-003-1891-z
|View full text |Cite
|
Sign up to set email alerts
|

The prostaglandins epoprostenol and iloprost increase left ventricular contractility in vivo

Abstract: Left ventricular contractility is increased in vivo by epoprostenol and iloprost but not by adenosine or sodium nitroprusside at equipotent hypotensive dose. A contribution of sympathetic reflex activation of cardiac nerves on the increase in left ventricular contractility cannot be completely ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
7
34
0
2
Order By: Relevance
“…This is in concordance with Rex et al, 22 who tested a low dose of iloprost in pigs subjected to acute pulmonary hypertension and did not show any improvement in RV function. This is also supported by Kisch-Wedel et al, 10 who reported a positive inotropic response in the LV of the pig during administration of iloprost at a supratherapeutic dose. Nitroprusside, which is a systemic arterial vasodilator, was titrated to produce the same drop in MAP as was and cardiac output (CO; B) in percent difference from placebo treatment after injection of Ilo10 and Ilo100.…”
Section: 19supporting
confidence: 75%
“…This is in concordance with Rex et al, 22 who tested a low dose of iloprost in pigs subjected to acute pulmonary hypertension and did not show any improvement in RV function. This is also supported by Kisch-Wedel et al, 10 who reported a positive inotropic response in the LV of the pig during administration of iloprost at a supratherapeutic dose. Nitroprusside, which is a systemic arterial vasodilator, was titrated to produce the same drop in MAP as was and cardiac output (CO; B) in percent difference from placebo treatment after injection of Ilo10 and Ilo100.…”
Section: 19supporting
confidence: 75%
“…64,65 Afterload reduction, however, cannot be achieved in many cases, but the increased right ventricular wall thickness and reversal of a fetal gene expression program have not yet been investigated as potential targeted treatments. Chronic intravenous epoprostenol infusion therapy in patients with pulmonary arterial hypertension appears to improve right ventricular function 66,67 (although dilation and hypertrophy may not reverse over a 1-year period of observation 68 ), and the effects of the endothelin receptor antagonist bosentan on echocardiographic right ventricular parameters have also suggested a similar improvement in right ventricular function. 69 However, the specific myocardial effects of these or other therapies for pulmonary arterial hypertension remain incompletely understood.…”
Section: Treatment Of Right Ventricular Dysfunctionmentioning
confidence: 99%
“…45 And although it is quite possible that these observations are correct, it is of concern that the prostanoids have inotropic effects which results in a marked increase in stroke work of the right ventricle. 47,48 The experience with inotropic agents in patients with LV failure, 49 including intravenous epoprostenol, 50 showed an improvement in cardiac output that translated into an improvement in exercise tolerance in the short term, but an increase in mortality in the long term. This lesson requires us to remain diligent of this possibility in PAH as well.…”
Section: Prostacyclinsmentioning
confidence: 99%